Proceedings of the 23rd International Conference on Industrial Engineering and Engineering Management 2016 Theory and Application of Industrial Engineering - Qi, Ershi; Shen, Jiang; Dou, Runliang; SpringerLink (Online service) (Paris : Atlantis Press : Imprint: Atlantis Press, 2017)
International Conference on Industrial Engineering and Engineering Management is sponsored by Chinese Industrial Engineering Institution, CMES, which is the unique national-level academic society of Industrial Engineering. The conference is held annually as the major event in this area. Being the largest and the most authoritative international academic conference held in China, it supplies an academic platform for the experts and the entrepreneurs in International Industrial Engineering and Management area to exchange their research results. Many experts in various fields from China and foreign countries gather together in the conference to review, exchange, summarize and promote their achievements in Industrial Engineering and Engineering Management fields. Some experts pay special attention to the current situation of the related techniques application in China as well as their future prospect, such as Industry 4.0, Green Product Design, Quality Control and Management, SupplyChain and logistics Management to cater for the purpose of low-carbon, energy-saving and emission-reduction and so on. They also come up with their assumption and outlook about the related techniques' development. The proceedings will offer theatrical methods and technique application cases for experts from college and university, research institution and enterprises who are engaged in theoretical research of Industrial Engineering and Engineering Management and its technique's application in China. As all the papers are feathered by higher level of academic and application value, they also provide research data for foreign scholars who occupy themselves in investigating the enterprises and engineering management of Chinese style.
1.Selection Of Port Enterprise Logistics Service Providers Based On The Combination Weighting-Grey Synthetic Decision-Making Method -- 2.Application of evaluation of aircraft material demand forecasting method and mining of association rules -- 3.Research on the Selection of Business-to-Customer e-commerce Logistics Model Based on Analytic Hierarchy Process Method -- 4.Content Framework and Evaluating Method of the Energy Efficiency Assessment Standard for Machining period -- 5.Combining Problem and Lecture Based Learning for Production System Modeling and Simulation Course in Industrial Engineering Education -- 6.Schedule Risk Management of IT Outsourcing Project Using Negotiation Mechanism -- 7.The Effect of Reciprocity on Revenue Sharing Contract Coordination and its Dynamics -- 8.Intelligent Rescheduling System for Steelmaking and Continuous Casting Production -- 9.Application of RCA to the Data Analysis in Medication Errors of the TPR System -- 10.An Investigation of Adverse Events in Medication Processes by HFACS and Conditional Probability -- 11.Adaptive Grasping and Adjusting Method of Virtual Hand Gestures with Semantics Information for Virtual Assembly -- 12.Dynamic Medical Risk Assessment based on Bow-tie Approach and Bayesian Network -- 13.Rational Thinking of the Marketing Strategy Based on Customer Equity -- 14.An Empirical Study on Manufacturing Strategy Formulation in Turbulent Environment: Dealing with Changes and Uncertainties -- 15.The Impacts of Trust Relationship on Knowledge Absorptive Capacity: An Empirical Study from Service Outsourcing Enterprises -- 16.Determination of price and warranty length under claim rate of customer -- 17.Research on Module Construction based on Product Lifecycle Management -- 18.Logistics Distribution Path Planning Based On Genetic Algorithm -- 19.Research on the Mechanism of Risk Cascading Propagation across Interdependent R&D Networks -- 20.Research on Capabilities-based Optimization Matching of Vessel Maintenance Support Equipment -- 21.Analysis on Warship Technology Supportability Equipment System-of-Systems Based on System Dynamics -- 22.Simulation Model of Rail Transshipment System in Hydropower Development Project -- 23.The Application Of Six Sigma Theory In The Secondary Hospital Management -- 24.Research on Parameter Optimization of ant colony algorithm based on genetic algorithm -- 25.Multi-objective Integrated Optimization Problem of Preventive Maintenance Planning and Flexible Job-Shop Scheduling -- 26.Cost-sensitive Association Rule Modeling for Predicting Sequential Event -- 27.Study on the Improved PSO Algorithm Used in Coal Mine Safety Resource Allocation -- 28.Research on the Improving Design of Laminating Machine Based on Lean Six Sigma -- 29.A Method of Quality Evaluation for Complexity Equipment Manufacturing and Service Based on Process Area and its Reliability & Validity Analysis -- 30.Analyzing "Made in China 2025" Under theBackground of "Industry 4.0" -- 31.Study on the Implementation Strategy of Liaoning Manufacturing Collaborative Innovation System Based on "Made in China 2025" -- 32.Layout Analysis and Design of the Spindle Box Processing Workshop -- 33.Empirical Research on Production Leveling of Domestic Car -- 34.Exploration and Practice of Car Industry Lean Culture Construction -- 35.The study about intelligent manufacturing resource allocation efficiency based on mutual information criterion -- 36.Social Insurance Expenditure and Future Trend in China -- 37.A Two-Level Principal-Agent Model for Schedule Risk Control of IT Outsourcing Project Based on Genetic Algorithm -- 38.An Empirical Analysis of Influence of Capital Allocation Efficiency on Performance in Listing Corporation -- 39.The Game about Competition and Cooperation in Port Group -- 40.The factors Influencing Dwelling-Type Choices of residents in the Old Industrial District: an Investigation based on the Logistic Model -- 41.A management method ofaccounts receivable based on credit rating for rail equipment manufacturing industry -- 42.The Research of Doctors Recommendation Algorithm -- 43.Resource Constrained Project Scheduling Optimization With Robust Objective Under Stochastic Duration Of Activities -- 44.Dynamic scheduling of public bicycles based on artificial bee colony algorithm -- 45.Web service classification approach with an integrated similarity measure -- 46.How to Optimize Production and Carbon Resources under Cap and Trade -- 47.The Development About Social Network Analysis And The Review About Its -- 48.Gallbladder Diagnosis and Importance Analysis based on Bayesian Network -- 49.The Effect of Dynamic Capabilities on International Performance of Chinese Universities -- 50.Researching The Role Of Online Movie Reviews Based On User Classification -- 51.Analysis and Simulation Application for Enterprise Populations M&A Based on Predator-prey Model -- 52.Research on Mechanism of Early Warning of Health Management Based onCloud Computing and Big Data -- 53.Research on Early Safety Warning Evaluation Based on Multi-hierarchy Fuzzy AHP in Civil Aviation Airport -- 54.Modeling and Analysis of the Customer Checkout Process with Flexible Servers for a Retail Store -- 55.An Integrated Strategy for Information Security:Outsourcing and In-house.
Keywords: Industrial engineering; Production engineering; Technological innovations; Electronic data processing -- Management; Engineering design; Business logistics; Industrial and Production Engineering; Innovation and Technology Management; IT Operations; Engineering Design; Supply Chain Management